EFFECTS OF LAMIVUDINE ON BIOCHEMICAL INDICES IN RATS. (2014)
Lamivudine (L(-)21,31–dideoxy–3-thiacytidine) is an antiretroviral drug which exhibits tissue toxicity leading to peripheral neuropathy and parkinsonism. The exact mechanism of cytotoxicity and effects on target tissues are not well understood. This study was designed to elucidate the effects of lamivudine on biochemical indices in the liver, kidney and brain of rats. Female Wistar rats (180-200g) were randomly assigned into 5 groups of 6 rats each treated orally for 45 days with normal saline (Control), 4 mg/kg, 20 mg/kg, 100 mg/kg and 500 mg/kg lamivudine respectively. Rats were sacrificed after 12 hours fast and blood (6 mL) collected. Serum obtained was used for biochemical analysis. Serum Alanine and Aspartate Aminotransferases (ALT and AST), Quinine Oxidase (QO), γ–GlutamylTransferase(GGT), urinary trehalase activities as well as urinary creatinine and protein were determined by spectrophotometric techniques while urinary magnesium (Mg2+) level was determined by atomic absorption spectrophotometry. In the liver, kidney and brain, the activities of Superoxide Dismutase (SOD), Glutathione-S-Transferase (GST) and levels of malondialdehyde (MDA, index of lipid peroxidation) were determined. Histology of the liver and kidney was assessed using hematoxylin and eosin stain. Data were analysed using ANOVA at p=0.05. Lamivudine (500 mg/kg) produced significant increases in the activities of serum ALT, AST, GGT and QO (33.2±3.9, 56.4±7.2, 16.3±1.8 IU/L and 10.1±1.7 Baier’s Unit (BU)) relative to controls (21.3±1.5, 42.6±1.9, 11.1±0.7 IU/L and 4.9±1.0 BU) respectively. The drug at 20, 100 and 500 mg/kg increased hepatic GGT activities by 3.1, 4.0 and 5.2 folds while hepatic GST increased by 1.7, 1.8 and 2.0 folds relative to controls respectively. Renal GST activities significantly increased in lamivudine (100 and 500 mg/kg) treated rats (3.15±0.12, 3.57±0.23x 10-2 U/mg protein) relative to control (1.74±0.23x 10-2 U/mg protein). The level of hepatic MDA in control was 0.06±0.01 nmol/mg protein while lamivudine at 100 and 500 mg/kg significantly increased MDA levels (0.17±0.03, 0.22±0.04 respectively). Also, lamivudine at 100 and 500 mg/kg significantly increased renal MDA levels by 125% and 189% respectively when compared with the control. The activity of hepatic SOD in control was 9.9±0.7 U/mg protein. Treatment with lamivudine (20, 100 and 500 mg/kg) significantly increased SOD activities (14.7±1.5, 18.4±1.2, 16.5±1.3 U/mg protein). Similar trend was observed for renal SOD UNIVERSITY OF IBADAN LIBRARY activities of rats treated with lamivudine. Administration of lamivudine at 100 mg/kg significantly increased urinary trehalase activity (324.1±15.3 vs 157.8±18.6 U/mg per ml), urinary Mg2+ concentration (8.6±0.4 vs 4.8±0.5x10-3/mg/ml) and urinary protein (2.9±0.29 mg/ mlvs 1.4±0.14mg/ml). However, there were no significant differences in the values of brain SOD, MDA, and urinary creatinine in lamivudine-treated animals relative to controls. Histological sections of rats treated with lamivudine (100 and 500 mg/kg) showed visible lesions in the liver (hydropic degeneration) and kidney (cortical congestions). Repeated administration of lamivudine altered biochemical indices accompanied by visible histologic effects in the liver and kidney of the rats. The biochemical alterations appear to be mediated by oxidative stress. Keywords: Biochemical Indices, Cytotoxicity, Lamivudine, Oxidative stress. Word count: 484